Penyelesaian Wanprestasi Antara Bank dan Nasabah Melalui Mediasi di BPR Werdhi Sedana Gianyar - Vijayetta Sriratih Viswari; Nella Hasibuan O'leary; Desak Gde Dwi Arini (Jurnal Analogi Hukum, 2021)
Increased public trust and interest in using bank services has resulted in many default disputes where legal protection of customer rights and regulations regarding dispute resolution that occur at a bank are required. Banking mediation is an option that is often used by banks to resolve default disputes that occur. As for the formulation of the problem (1) How is the legal protection of customers at BPR Werdhi Sedana Gianyar? (2) How is the settlement of default at BPR Werdhi Sedana Gianyar? The research used in the writing of this thesis uses empirical legal research by linking existing laws and regulations and the results of case studies. In the results of this study, the things that cause default at BPR Werdhi Sedana Gianyar, namely a decrease in turnover or bankruptcy which causes the debtor to be unable or late in fulfilling their obligations according to the agreed or determined time. Settlement of defaults used by BPR Werdhi Sedana Gianyar, namely by means of preventive (prevention) and repressive ways by issuing notification letters of arrears and warning letters, if the debtor has still not paid off his obligations, the last resort is by confiscation.